Nup98 regulates bipolar spindle assembly through association with microtubules and opposition of MCAK - Marie K. Cross; Maureen A. Powers (2011)
During mitosis, the nuclear pore complex is disassembled and, increasingly, nucleoporins are proving to have mitotic functions when released from the pore. We find a contribution of the nucleoporin Nup98 to mitotic spindle assembly through regulation of microtubule dynamics. When added to Xenopus extract spindle assembly assays, the C-terminal domain of Nup98 stimulates uncontrolled growth of microtubules. Conversely, inhibition or depletion of Nup98 leads to formation of stable monopolar spindles. Spindle bipolarity is restored by addition of purified, recombinant Nup98 C-terminus. The minimal required region of Nup98 corresponds to a portion of the C-terminal domain lacking a previously characterized function. We show association between this region of the C-terminus of Nup98 and both Taxol-stabilized microtubules and the microtubule-depolymerizing mitotic centromere-associated kinesin (MCAK). Importantly, we demonstrate that this domain of Nup98 inhibits MCAK depolymerization activity in vitro. These data support a model in which Nup98 interacts with microtubules and antagonizes MCAK activity, thus promoting bipolar spindle assembly.